Quantification of oxidative stress in Saccharomyces pastorianus propagation: Gene expression analysis using quantitative reverse transcription polymerase chain reaction and flow cytometry - Beugholt, Alexander; Büchner, Kai; Geier, Dominik Ulrich; Becker, Thomas (Frontiers in Chemical Engineering, 2022)
When confronted with environmental stress, yeast cell reacts, among others, by modifying the expression of specific genes. In this study, gene expression was analyzed via RT-qPCR to quantify the oxidative stress of Saccharomyces pastorianus during yeast propagation as a reaction to different aeration levels. Target genes were identified, and a reference gene system was developed. Fermentation experiments were conducted in shaking flasks, applying different shaking speeds to generate various aeration efficiencies. The cells were sampled at different propagation stages and, additionally to the expression study, analyzed by flow cytometry after staining with dihydroethidium (DHE) to quantify reactive oxygen species (ROS) inside the cells. The results indicate that high oxygen fermentation conditions led to an increased expression of the catalase-A gene CTA1 during propagation. Furthermore, the determination of cell internal ROS shows increasing oxidative stress over the process in accordance with the RT-qPCR measurements